Seasonal variability of carbon in humic-like matter of ambient size-segregated water soluble organic aerosols from urban background environment. (January 2018) - Frka, Sanja; Grgić, Irena; Turšič, Janja; Gini, Maria I.; Eleftheriadis, Konstantinos
Abstract: Long-term measurements of carbon in HUmic-LIke Substances (HULIS-C) of ambient size-segregated water soluble organic aerosols were performed using a ten-stage low-pressure Berner impactor from December 2014 to November 2015 at an urban background environment in Ljubljana, Slovenia. The mass size distribution patterns of measured species (PM - particulate matter, WSOC - water-soluble organic carbon and HULIS-C) for all seasons were generally tri-modal (primarily accumulation mode) but with significant seasonal variability. HULIS-C was found to have similar distributions as WSOC, with nearly the same mass median aerodynamic diameters (MMADs), except for winter when the HULIS-C size distribution was bimodal. In autumn and winter, the dominant accumulation mode with MMAD at ca. 0.65 μm contributed 83 and 97% to the total HULIS-C concentration, respectively. HULIS-C accounted for a large fraction of WSOC, averaging more than 50% in autumn and 40% in winter. Alternatively, during warmer periods the contributions of ultrafine (27% in summer) and coarse mode (27% in spring) were also substantial. Based on mass size distribution characteristics, HULIS-C was found to be of various sources. In colder seasons, wood burning was confirmed as the most important HULIS source; secondary formation in atmospheric liquid water also contributed significantly, as revealed by the MMADs of the accumulation mode shifting to larger sizes. The distinct difference between the spring and summer ratios of HULIS-C/WSOC in fine particles (ca. 50% in spring, but only 10% in summer) indicated different sources and chemical composition of WSOC in summer (e.g., SOA formation from biogenic volatile organic compounds (BVOCs) via photochemistry). The enlarged amount of HULIS-C in the ultrafine mode in summer suggests that the important contribution was most likely from new particle formation during higher emissions of BVOC due to the vicinity of a mixed deciduous forest; the higher contribution of HULIS-C in the coarse mode demonstrated that beside soil erosion other sources, such as pollen and plant fragments, could also be responsible. Graphical abstract: Highlights: Long-term measurements of water soluble HULIS carbon (HULIS-C) in ambient aerosols. Strong seasonal variability of size-resolved WSOC and HULIS-C. Except for winter, mass size distributions of HULIS-C were tri-modal. Main contribution to accumulation mode from wood burning in winter-autumn. Substantial contribution of ultrafine and coarse modes to HULIS-C in spring-summer.